Impact of Liquidity Ratio, Dividend on Share Price: A Study of Food and Allied, Engineering, and Pharmaceuticals and Chemicals Industries in Bangladesh - Md Raihan Habib (Mustard Journal De Ecobusin, 2024)
This paper involves the analysis of the effects of liquidity ratios and dividends on share price in three industries, which include engineering, food and allied, as well as pharmaceuticals and chemicals. The total sample will be 425 observations that will be sampled based on the financial documents of 85 companies. Annual report and Lanka Bangla database were the source of data covering the period between 2016 and 2020. The analysis shows that there is statistically significant negativity between current ratio and share price, and quick ratio and share price. On the other hand, cash ratio has a strong positive linkage with share price, and the dividends also have a strong positive impact. The research is conducted on secondary data only, and this is the main limitation of the investigation; due to the inability to find information about some companies, the sample size was minimized. The study will make important contributions to both academic and practitioner communities because by clarifying the relationship between share price, liquidity measures, and dividends, the study will be useful in the decision-making process of investors, shareholders, creditors, and other stakeholders.